Aquaponics Food Production Systems Combined Aquaculture and Hydroponic Production Technologies for the Future - Goddek, Simon; Joyce, Alyssa; Kotzen, Benz; Burnell, Gavin M. (Springer International Publishing : Imprint: Springer, 2019)
This open access book, written by world experts in aquaponics and related technologies, provides the authoritative and comprehensive overview of the key aquaculture and hydroponic and other integrated systems, socio-economic and environmental aspects. Aquaponic systems, which combine aquaculture and vegetable food production offer alternative technology solutions for a world that is increasingly under stress through population growth, urbanisation, water shortages, land and soil degradation, environmental pollution, world hunger and climate change.